A Study of International Curriculum in Global School to Strengthen Multicultural Value - Nurdiyanti, Aina; Khaedir, Muh; Hotimah, Iis Husnul (Jurnal Civicus, 2024)
The purpose of this research is to find out the Implementation of Global Citizenship Education for Celebes Global School students. Global citizenship education is a prerequisite for citizens to be able to participate in the differences of modernity, which requires skills that citizens must possess. This research method uses case studies through observation and in-depth interviews. The results of the study show that Celebes Global School Makassar implements global citizenship education by organizing student exchanges with the aim of learning from each other's cultures that represent Western (Australian) and Eastern (Indonesian) cultures. Celebes Global School, in collaboration with intra-school organizations, regularly celebrates interfaith holidays together such as Hijriyah New Year, Christian New Year and Chinese New Year. Celebes Global School Makassar realizes the importance of global citizenship education by organizing international standard education through implementing curriculum integration between Indonesia and Australia.